Does the John Bates Clark Medal Boost Subsequent Productivity and Citation Success? - Ho Fai Chan; Bruno S. Frey; Jana Gallus; Benno Torgler (Center for Economic Studies and ifo Institute (CESifo), 2013)
Despite the social importance of awards, they have been largely disregarded by academic research in economics. This paper investigates whether a specific, yet important, award in economics, the John Bates Clark Medal, raises recipients' subsequent research activity and status compared to a synthetic control group of non-recipient scholars with similar previous research performance. We find evidence of positive incentive and status effects that raise both productivity and citation levels.
Keywords: A13; C23; M52; 330; awards; incentives; research; John Bates Clark Medal; synthetic control method